2015
DOI: 10.7824/rbh.v14i2.405
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia e fitotoxicidade de herbicidas aplicados para manejo de plantas daninhas infestantes do trigo

Abstract: -The objective of this paper was to identify alternatives for the chemical handling of weeds that infect wheat, as well as verifying the phytotoxicity of herbicides on the crop. The experiment was carried out in randomized blocks, organized in a factorial design of 2x 13, with four repetitions. The wheat crops were allocated to factor A (Quartzo and Pioneiro) and the herbicides to factor B (iodosulfuron -0,100 kg ha -1 ; imazapic + imazapyr -0,140 kg ha -1 ; clomazone 0,800 L ha -1 ; imazethapyr + imazapic -1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
5
0
5
Order By: Relevance
“…Barley ears length showed reduced values with the application of 2,4-D amine at the first node stage and after the first node of the crop, compared to the application of 2,4-D choline after the first node, compared to the other treatments for thousand-grain weight. In a previous study, an average increment of 3% was observed in the thousand-grain weight of barley cultivars MN610 and Crioula treated with the herbicide 2,4-D amine, compared to the witness without application of the product (Galon et al, 2014). Viecelli et al (2019) found no change in the thousand-grain weight of wheat when treated with 2,4-D amine at the third tiller emission stage.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Barley ears length showed reduced values with the application of 2,4-D amine at the first node stage and after the first node of the crop, compared to the application of 2,4-D choline after the first node, compared to the other treatments for thousand-grain weight. In a previous study, an average increment of 3% was observed in the thousand-grain weight of barley cultivars MN610 and Crioula treated with the herbicide 2,4-D amine, compared to the witness without application of the product (Galon et al, 2014). Viecelli et al (2019) found no change in the thousand-grain weight of wheat when treated with 2,4-D amine at the third tiller emission stage.…”
Section: Resultsmentioning
confidence: 84%
“…Agrar., Recife, v.17, n.2, e1850, 2022 5/9 and only 2,4-D choline was harmful to this variable studied in the tillering period and after the first node of barley plants, compared to plants without the application of herbicides. Although they found reduced percentage of phytotoxicity, Galon et al (2014) also found reduced ears number when applying 2,4-D amine to barley cultivars MN610 and Crioula.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…O tratamento com o herbicida profoxidim proporcionou maior nível fitotóxico quando comparado ao controle, seguido pelo tratamento com o herbicida bispiribaque-sódico, Galon et al, (2015) avaliando a eficácia e fitotoxicidade de diferentes herbicidas aplicados na cultura do trigo para controle de plantas daninhas, observaram que os herbicidas imazethapyr + imazapic, clomazone e imazapic + imazapyr apresentaram maior fitotoxicidade na cultura.…”
Section: Resultsunclassified